Building Mutual Understanding: How Children with Autism Spectrum Disorder Manage Interactional Trouble. (7th March 2016) - Dindar, Katja; Korkiakangas, Terhi; Laitila, Aarno; Kärnä, Eija
Abstract : Children with autism spectrum disorder (ASD) are vulnerable to interactional trouble: difficulties in speaking, hearing and understanding. Prior conversation analytic (CA) work has examined how interactional trouble gets repaired mostly in verbal interactions among neurotypical speakers. Non-CA examinations have mainly been concerned with how children with ASD respond to others' requests for clarification. Little is known about how children with ASD might manage and initiate solving interactional difficulties. Drawing on CA, this study reports on a sample of approximately 46 hours of video involving school-aged children with ASD and their adult co-participants. The analysis shows that children use both verbal and nonverbal resources to initiate the management of apparent trouble. However, the children are occasionally unable to effectively communicate the particular source of difficulty to the co-participants. The study suggests the co-participants' active and sensitive facilitation as a resource for building mutual understanding.